Experimental Study of Mechatronic System On Control of Air Flow Temperature - Asmara Yanto; Adriyan Adriyan; Rozi Saferi; M. Hanif Al Hafizh (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
In this work, an experimental study of a mechatronic system on control of airflow temperature has been conducted to identify the characteristics of the system. The system is tested by several reference temperatures from the monitor panel that programmed on the computer. The measurement of the output temperature by the sensor that is expected to be the same as the reference temperature is also displayed on the same monitor panel. While the measurement of AC power consumption by an actuator in the form of a heater is carried out by measuring the AC voltage on the heater during control. This voltage is measured with a computer-based oscilloscope. Based on the test results, with the initial temperature around the room temperature and reference temperature, the system time constant can be identified. This time constant value is obtained based on the output temperature graph which is identical to the first-order system response. Thus, this experimental study succeeded in identifying the characteristics of the system in the form of a time constant and the system was identified as identical to the first order system.